A new species of Gymnopus sect. Androsacei (Omphalotaceae, Agaricales) from China - Li, Ji-Peng; Song, Bin; Feng, Zhan; Wang, Jing; Deng, Chun-Ying; Yang, Yi-Hua (Phytotaxa, 2021)
A new species of Gymnopus sect. Androsacei, namely, G. pallipes is described and illustrated based on morphological and molecular phylogenetic evidence. It is characterized by marasmioid basidiomata, a dark brown to reddish brown pileus becoming dull white to yellowish grey with age, whitish to pale yellow stipe and presence of rhizomorphs. Phylogenetic analyses support it as a new species within Gymnopus sect. Androsacei. The detailed morphological description, colour photos of basidiomata, and line drawings of microcharacters are presented and delimitation characters from similar species are discussed. A key to the known species of Gymnopus s. str. from China is also provided.